The effects of noncoding aquaporin-4 single-nucleotide polymorphisms on cognition and functional progression of Alzheimer's disease - Burfeind, Kevin G; Murchison, Charles F; Westaway, Shawn K; Simon, Matthew J; Erten-Lyons, Deniz; Kaye, Jeffrey A; Quinn, Joseph F; Iliff, Jeffrey J (Alzheimer's & dementia : translational research & clinical interventions, 2017)
Abstract Introduction The glymphatic system is a brain-wide perivascular network that facilitates clearance of proteins, including amyloid β, from the brain interstitium through the perivascular exchange of cerebrospinal fluid and interstitial fluid. The astrocytic water channel aquaporin-4 (AQP4) is required for glymphatic system function, and impairment of glymphatic function in the aging brain is associated with altered AQP4 expression and localization. In human cortical tissue, alterations in AQP4 expression and localization are associated with Alzheimer's disease (AD) status and pathology. Although this suggests a potential role for AQP4 in the development or progression of AD, the relationship between of naturally occurring variants in the human AQP4 gene and cognitive function has not yet been evaluated. Methods Using data from several longitudinal aging cohorts, we investigated the association between five AQP4 single-nucleotide polymorphisms (SNPs) and the rate of cognitive decline in participants with a diagnosis of AD. Results None of the five SNPs were associated with different rates of AD diagnosis, age of dementia onset in trial subjects. No association between AQP4 SNPs with histological measures of AD pathology, including Braak stage or neuritic plaque density was observed. However, AQP4 SNPs were associated with altered rates of cognitive decline after AD diagnosis, with two SNPS (rs9951307 and rs3875089) associated with slower cognitive decline and two (rs3763040 and rs3763043) associated with more rapid cognitive decline after AD diagnosis. Discussion These results provide the first evidence that variations in the AQP4 gene, whose gene product AQP4 is vital for glymphatic pathway function, may modulate the progression of cognitive decline in AD.